Pembuatan Multimedia Pembelajaran Berbasis Bilingual Pada Materi Prosedur Penanganan Guest Laundry Di Akomodasi Perhotelan - Zamzami, Amalia; Rohaeni, Neni; Rinekasari, Nenden Rani (FamilyEdu: Jurnal Pendidikan Kesejahteraan Keluarga, 2019)
This research based on the limitation of primary school students in their mastery of the material handling procedures guset laundry a result of the use of media which still need innovation, so it needs he made media that are amenable to teaching material. This study aims to create multimedia learning that could help students in mastering foreign terms in the material handling procedures guest laundry. Methods used research and development, with a model ADDIE was, namely analysis, design, development, implementation, and evaluation. the participants in this study consisting of the people of the media and material laundry. An instrument used in this research was interview guidelines, observation guidelines and formats of expert judgement. findings the result of the research based on interview and observation shows the lack of means of learning which he can be quite handling guest of the procedure in their experiences using the term of the activities of many foreign speak English. Design stage starts from the preparation of the multimedia identity learning bilingual, the manufacture of synopsis, treatment and storyboard. the production process done based of design have been made. The results of expert judgement done by media expert and the matter laundry obtained that multimedia learning bilingual that have been made be in the reasonable used a supporting media learning. Recommendations that can be communicated from the result of this research, it is expected that educator can use multimedia learning as media innovation, researchers can be sanctioned for next pursue multimedia learning related to the learning bilingual as a medium learning handling procedures guest laundry.